THE ROLE OF MOUTH BREATHING ON DENTITION DEVELOPMENT AND FORMATION - Zornitsa Valcheva; Hristina Arnautska; Mariana Dimova; Gergana Ivanova; Iliyana Atanasova (Journal of IMAB, 2018)
Introduction: The influence of mouth breathing on the development of the dentition and dento-facial deformities is a problem causes concerns among the medical specialists. Mouth breathing has a major impact on the development of the maxillo-facial region, occlusion and muscle tonus. Aim: The aim of this study is to assess the relationship between etiological factors, pathogenesis and disturbances in mastication in mouth breathing patients. Material and methods: For this article, data is obtained from 43 medical, literary sources. Results: Literature review demonstrated that mouth breathing habit affects mostly children aged 7 - 12 years. In the vast majority of studies, the authors established a relation between mouth breathing and the development of maxillo-facial region and occlusion. The malocclusions described include a distal occlusion, anterior open bite, increase overjet, posterior crossbite, crowding and average incisors inclination disturbances. These clinical conditions become more complicated in the late-mixed and permanent dentition if mouth breathing continues to persist. Conclusion: The habitual mouth breathing is a great medical problem nowadays. An increasing numbers of patients with this condition although the development of technology for early diagnostic is embarrassing. This condition is strongly related with different malocclusions such as anterior open bite, overjet, distal occlusion, underdeveloped and narrow upper jaw, increased anterior facial height.